2023
DOI: 10.21203/rs.3.rs-2366052/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Umbilical cord mesenchymal stem cell-derived apoptotic extracellular vesicles ameliorate cutaneous wound healing in type 2 diabetic mice via macrophage pyroptosis inhibition

Abstract: Background: Delayed healing of diabetic cutaneous wounds is one of the most common complications of type 2 diabetes mellitus (T2DM), which can bring great distress to patients. In diabetic patients, macrophages accumulate around skin wounds and produce NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) inflammasomes, which in turn undergo pyroptosis and produce inflammatory factors such as interleukin-1β that affect wound healing. Although our previous study revealed that apoptotic extracellular vesicle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 205–208 A study by Wang et al demonstrated that ApoEVs derived from UCMSCs improved wound healing in db/db mice by suppressing the level of pyroptosis-associated proteins such as NLRP3, cleaved caspase-1, GSDMD, IL-1 and IL-18. 144 The authors showed that NLRP3, Caspase-1, GSDMD and F4/80 co-localized in pyroptotic BMDMs and ApoEV treatment significantly reduced the number of positive cells and fluorescence intensity in LPS/ATP-induced macrophages. Research investigations have shown that higher blood sugar levels may result in macrophage oxidative stress through the generation of excessive ROS in oxidative phosphorylation.…”
Section: Suppressing Pyroptosis-dependent Signaling In Therapeutic Re...mentioning
confidence: 97%
See 1 more Smart Citation
“… 205–208 A study by Wang et al demonstrated that ApoEVs derived from UCMSCs improved wound healing in db/db mice by suppressing the level of pyroptosis-associated proteins such as NLRP3, cleaved caspase-1, GSDMD, IL-1 and IL-18. 144 The authors showed that NLRP3, Caspase-1, GSDMD and F4/80 co-localized in pyroptotic BMDMs and ApoEV treatment significantly reduced the number of positive cells and fluorescence intensity in LPS/ATP-induced macrophages. Research investigations have shown that higher blood sugar levels may result in macrophage oxidative stress through the generation of excessive ROS in oxidative phosphorylation.…”
Section: Suppressing Pyroptosis-dependent Signaling In Therapeutic Re...mentioning
confidence: 97%
“… 215 ApoEVs derived from UCMSCs have been shown to effectively inhibit the accumulation of ROS, mitigate the generation of OS in macrophages and alleviate the occurrence of pyroptosis. 144 It has been demonstrated that the administration of ApoEVs is effective in modulating different types of cell death in a variety of cell types. Therefore, UCMSCs may provide a novel therapy for treating T2D-mediated wound healing and extend our understanding of the regulation of cell death.…”
Section: Suppressing Pyroptosis-dependent Signaling In Therapeutic Re...mentioning
confidence: 99%